2020
DOI: 10.1007/s11627-020-10056-1
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation and essential oil characterization of Plectranthus amboinicus (Lour.) Sprengel, an aromatic medicinal plant

Abstract: Plectranthus amboinicus (Loureiro) Sprengel is a therapeutically valued herb highly sought by various industries. This has led to its uncontrolled harvest from the wild leading to the risk of extinction. As an alternative, commercial propagation of P. amboinicus is desirable to avoid further depletion of wild populations. This paper describes the establishment of an efficient protocol for the multiplication, rooting and acclimatization of P. amboinicus. The greatest frequency of shoot multiplication of P. ambo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Interestingly, in vitro cultivation significantly affected EO composition that may be favored by the high chemical plasticity reported for tansy (Lawrence 2000). Like in some other reports (Arumugam et al 2020), in EO obtained from in vitro cultivated plants, a significantly greater number of chemical compounds was detected, as compared to that of wild-grown tansy (88 vs. 65, respectively). In vitro cultivation conditions also enhanced the accumulation of sesquiterpenes with respect to EO from field-grown "mother" plants, with a similar portion of identified monoterpene and sesquiterpene compounds.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, in vitro cultivation significantly affected EO composition that may be favored by the high chemical plasticity reported for tansy (Lawrence 2000). Like in some other reports (Arumugam et al 2020), in EO obtained from in vitro cultivated plants, a significantly greater number of chemical compounds was detected, as compared to that of wild-grown tansy (88 vs. 65, respectively). In vitro cultivation conditions also enhanced the accumulation of sesquiterpenes with respect to EO from field-grown "mother" plants, with a similar portion of identified monoterpene and sesquiterpene compounds.…”
Section: Discussionsupporting
confidence: 76%
“…The chemical composition in this study differs slightly from the results obtained through other essential oils of P. amboinicus from other countries, i.e., in the EO from Paraiba, Brazil, where the principal compounds found were carvacrol (33.50), p-cymene (28.20%) and γ-terpinene (14.77%). While a study in India reported the caryophyllene, caryophyllene oxide, aromadendrene oxide, and selinene as the majority components (Vishnu et al, 2021), in Malaysia the main constituents of the P. amboinicus EOs were carvacrol (43-45%), g-terpinene (11-16%), and p-cymene (12-16%) (Arumugam et al, 2020), and in Taiwan, these were was carvacrol (61,5%), β-Caryophyllene (12.79%), γ-terpinene (8.51%) and p-cymene (9.42%) (Huang et al, 2019). The variation in the proportion and yield percentage of essential oils and their chemical composition can be due to the influence of agroecology and environmental conditions (Aguiar et al, 2015).…”
Section: Resultsmentioning
confidence: 98%
“…Integration of GA 3 alone or in combination with cytokinins or/and auxins is reported in several species of Lamiaceae. Arumugam et al (2020) [44] found that the combination of 4.44 µM BAP and 2.89 µM GA 3 allowed maximum elongation and shoot multiplication of Plectranthus amboinicus (Lour.) Sprengel, but generated a high percentage of vitroplants with abnormal morphological characters.…”
Section: Discussionmentioning
confidence: 99%